Pollution and potential ecological risk assessment of heavy metals around the active Bukit Mendi palm oil mill area, Bera Pahang, Malaysia / Mohd Zahari Abdullah and Nur Najiha Abdul Hadi - Abdullah, Mohd Zahari; Abdul Hadi, Nur Najiha (Universiti Teknologi MARA, 2022)
The study on the impact of palm oil mill processing activities on the environment of Bukit Mendi Palm Oil Mill was conducted by determining the distribution of six heavy metal concentrations Cadmium (Cd), Copper (Cu), Manganese (Mn), Lead (Pb), Iron (Fe) and Zinc (Zn) and the selected pollution indices. This study provided some information on the accumulation of heavy metals in the selected area and served to identify the potential sources contributing to these heavy metals. Soil samples were collected from eight sampling sites around the palm oil mill and analysed for the selected metals using ICP-OES. Three types of pollution indices were used to observe the pollution level of the area, namely Enrichment Factor (EF), potential ecological risk index (PERI), and Contamination Factor (CF) of heavy metal content. The average total concentration of the selected metals was found to increase in the order of Fe, Mn, Zn, Cd, Pb, and Cu. The metal Fe showed the highest metal content, followed by Mn at 1573.00 mg/kg and 154.00 mg/kg, respectively. The values of EF showed that the metal was unevenly distributed throughout the sampling areas, where heavy metal content ranged from minimal to extremely high enrichment. The potential ecological risk ranging from low to severe was observed in this study. The CF values revealed that the area was heavily contaminated with Cd and only slightly contaminated with Pb. The pollution indices determined in this study suggested that the study area was moderately contaminated with metals, and the metal Cd was found to be the only metal potentially posing an ecological risk to the area